Global distribution, evolutionary dynamics, and origins of wheat streak mosaic virus - Li, Dan; Song, Xi; Yang, Fang (Frontiers in Plant Science, 2025)
Wheat streak mosaic virus (WSMV), one of the major pathogens affecting global wheat production, causes severe yield losses. Although its global diversification has been reported, the evolutionary dynamics and phylogeographic patterns of WSMV remain poorly understood. In the present study, we systematically investigated the global distribution of WSMV by integrating genomic sequences and literature reports. Furthermore, we analyzed the evolutionary dynamics and phylogeography of WSMV using 104 complete genomes and 218 coat protein (CP) gene sequences. Our results revealed that WSMV is currently spreading across 26 countries on six continents. Maximum likelihood (ML) phylogenetic analyses delineated four genotypes: Genotype I (Mexican lineage), Genotype II (Iranian-specific lineage), Genotype III (Eurasian-North American lineage), and Genotype IV (U.S.-Australian-Iranian lineage). Bayesian phylodynamic analysis estimated a mean evolutionary rate of 3.023 × 10–4 substitution/site/year (95% HPD: 1.945 × 10-4-4.187 × 10-4), and suggested that WSMV may have emerged in Iran, with the time to the most recent common ancestor (tMRCA) around 1700 (95% HPD: 1521-1850), although the relatively weak temporal signal limits precise timing (R² = 0.0585). Hierarchical tMRCA estimates revealed progressive diversification: Turkey and the United States at 1730 (95% HPD: 1580-1854), European countries at 1952 (95% HPD: 1915-1983), Kazakhstan at 1949 (95% HPD: 1911-1983), Australia at 1972 (95% HPD: 1953-1991), and Brazil at 1994 (95% HPD: 1981-2005). Bayesian phylogeographic reconstruction suggested Iran as a likely origin based on current data, with dispersal to the United States in the mid-19th century (1852-1887; Bayes factors (BF) = 5.26, posterior probability (PP) = 0.48) and to Turkey in the 20th century (1909-1942; BF = 65.76, PP = 0.92), both of which subsequently served as secondary hubs for global dissemination. The findings that WSMV has undergone persistent evolutionary diversification over extended temporal scales, and continues to spread globally, providing a framework for enhanced surveillance and control strategies.